1989
DOI: 10.1063/1.101807
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature diamond deposition by microwave plasma-enhanced chemical vapor deposition

Abstract: Thin diamond films were deposited on silicon, MgO, fused silica, and soda lime silica glass at low temperature (the lowest temperature ∼365 °C) by microwave plasma-enhanced chemical vapor deposition. The films were identified as diamond by Raman spectroscopy. A Raman peak shift of several wave numbers to either lower or higher wave numbers due to the strain of the film is also observed. The film deposited on glass is highly transparent. The fine faceted crystals in the film are shown in scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…1,2 For the optical application, particularly, low temperature deposition of diamond film is inevitably required because of the low melting point of optical materials such as glass, NaCl, KBr, and so forth. [3][4][5] Despite this advantage, deposition rate and diamond quality have been reported to be inferior compared to the normal deposition technique ͑10 TorrϽtotal pressureϽ100 Torr͒ 3,6 because the low total pressure technique should give a low concentration of the diamond precursor. 4,5 The technique can enhance diamond film uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For the optical application, particularly, low temperature deposition of diamond film is inevitably required because of the low melting point of optical materials such as glass, NaCl, KBr, and so forth. [3][4][5] Despite this advantage, deposition rate and diamond quality have been reported to be inferior compared to the normal deposition technique ͑10 TorrϽtotal pressureϽ100 Torr͒ 3,6 because the low total pressure technique should give a low concentration of the diamond precursor. 4,5 The technique can enhance diamond film uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…4. However, the cross section offilm (11) looked like an amorphous structure, despite the fact that film (12) showed clear columnar crystal phases in its cross view. The film (8) deposited at 450°C in the eO/H2 system had definite cube-like characteristics and their crystal sizes were about 0.3-0.5 f1m.…”
Section: The Sem Images Of Obtained Filmsmentioning
confidence: 98%
“…12 In this paper, low temperature growth was attempted in both CO/H2 and CO/H2/ Ar systems. Polycrystalline diamond was synthesized in a CH 4 /H 2 /0 2 system at an average temperature of 400°C using a pulsed mode microwave plasma discharge system.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Attempts at nucleating diamonds on oxide materials using similar approaches have not been successful. 11,12 Patscheider 13 indicated that the SiO 2 layer will be preferentially etched away in the CVD process, resulting in rough surface that lowered the nucleation density. Rankin 14 proposed that nucleation of diamonds on SiO 2 still proceeded by surface reaction to form SiC intermediate layer.…”
Section: Introductionmentioning
confidence: 99%